2020
DOI: 10.1021/acs.inorgchem.0c03007
|View full text |Cite
|
Sign up to set email alerts
|

Hg2+ Significantly Enhancing the Peroxidase-Like Activity of H2TCPP/ZnS/CoS Nanoperoxidases by Inducing the Formation of Surface-Cation Defects and Application for the Sensitive and Selective Detection of Hg2+ in the Environment

Abstract: Exploring excellent peroxidase mimics with enhanced peroxidase-like activity is important to the construction of a fast, low-cost, and convenient colorimetric sensing platform for heavy ions. In this work, 5,10,15,20-tetrakis­(4-carboxyphenyl)­porphyrin (H2TCPP) was first used to modify ZnS/CoS and make it show better peroxidase-like activity. The metal-cation vacancies generated by Hg2+ contacting H2TCPP/ZnS/CoS further stimulate the catalytic activity. It is reported that the addition of Hg2+ usually causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Overall, the above strategies still require natural enzymes, which are generally expensive and sensitive to reaction conditions. As a kind of artificial analogue of enzymes, nanozymes are inorganic nanomaterials that possess enzyme-mimicking kinetic behaviors in the conversion of enzyme substrates to products, 24,25 allowing them to be widely used in environmental remediation, 26 molecular detection, 27,28 as well as biomedicine and therapeutics. 29 However, most of the current existing light/nanozyme systems are ascribed to photo-activated nanozymes or photo-responsive nanozymes.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the above strategies still require natural enzymes, which are generally expensive and sensitive to reaction conditions. As a kind of artificial analogue of enzymes, nanozymes are inorganic nanomaterials that possess enzyme-mimicking kinetic behaviors in the conversion of enzyme substrates to products, 24,25 allowing them to be widely used in environmental remediation, 26 molecular detection, 27,28 as well as biomedicine and therapeutics. 29 However, most of the current existing light/nanozyme systems are ascribed to photo-activated nanozymes or photo-responsive nanozymes.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figures 4c−e and S12, with the gradual increase of PBQ and TBA concentration, their relative activity gradually decreased, implying that in the catalytic reaction process, • O 2 − and • OH produced by H 2 O 2 and O 2 molecules were used as active intermediates for the catalytic reaction. 57,58 It is worth noting that with the increase of Hg 2+ concentration in the reaction system, the relative activity of the reaction system with PBQ as the free radical scavenger decreased by 18.92, 38.00, and 59.48%, with a higher degree of decrease, indicating that • O 2 − had a greater impact on the catalytic reaction at the reaction stage of high concentration of Hg 2+ . However, in the reaction system with TBA as the free radical scavenger, the relative activity in the presence of 1.0 and 10.0 μM Hg 2+ decreased only 27.62, and 24.71%, respectively, which was probably due to the self-quenching reaction between H 2 O 2 and • OH (reaction 1− 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Hg 2+ can generate stable HgS via the strong chelation with the S 2component in nanozymes, and the formed HgS inhibits the nanozymes' activity via replacing their active components and blocking reaction sites. 30,[45][46][47][48] Thus, Hg 2+ can effectively modulate the catalytical activity of nanozymes. For example, Fang et al found that CuS nanoparticles with peroxidase-like activity exhibited excellent selectivity and adsorption capacity for Hg 2+ (Figure 3C).…”
Section: Analytes Modulate Nanozyme Activitymentioning
confidence: 99%